O tratamento das demandas de massa nos Juizados Especiais Cíveis - Hermann, Ricardo Torres (2010)
This thesis demonstrates that the Small Claims Courts have the calling for the resolution of individual conflicts. It notes, based on case study that, however, these courts are faced with a lot of collective demands which are jeopardizing the functioning of these legal channels. Thus, it is proposed to reflect what are the appropriate measures to deal with this problem. It notes that the use of the Public Civil Action (similar to Class Action) is still incipient in the country, especially in the case of homogeneous individual rights (“direitos individuais homogêneos”). As a result, the paper points out the need to encourage the protection of such collective rights and how the class actions can absorb the individual actions that continue to be proposed on those issues. It concludes that individual homogeneous rights (“direitos individuais homogêneos”) can be considered typical collective rights (broadly) and should be protected by the Class Action. This study establishes that it is necessary to include a legal provision to give only to Public Civil Action Courts the competence to conduct concurrent individual and collective disputes, avoiding that they be proposed in the Small Claims Courts, because it’s not possible to use their own mechanisms of Public Civil Actions in these courts. It also indicates the importance of establishing the absolute competence of Small Claims Courts as a way of defining their appropriate expertise and formulate directions for handling the demands of mass, whether they are of collective or individual nature.